BMPR2 acts as a gatekeeper to protect endothelial cells from increased TGFβ responses and altered cell mechanics. - Christian Hiepen; Jerome Jatzlau; Susanne Hildebrandt; Branka Kampfrath; Melis Goktas; Arunima Murgai; Jose Luis Cuellar Camacho; Rainer Haag; Clemens Ruppert; Gerhard Sengle; Elisabetta Ada Cavalcanti-Adam; Kerstin G Blank; et al. (PLoS Biology)
Balanced transforming growth factor-beta (TGFβ)/bone morphogenetic protein (BMP)-signaling is essential for tissue formation and homeostasis. While gain in TGFβ signaling is often found in diseases, the underlying cellular mechanisms remain poorly defined. Here we show that the receptor BMP type 2 (BMPR2) serves as a central gatekeeper of this balance, highlighted by its deregulation in diseases such as pulmonary arterial hypertension (PAH). We show that BMPR2 deficiency in endothelial cells (ECs) does not abolish pan-BMP-SMAD1/5 responses but instead favors the formation of mixed-heteromeric receptor complexes comprising BMPR1/TGFβR1/TGFβR2 that enable enhanced cellular responses toward TGFβ. These include canonical TGFβ-SMAD2/3 and lateral TGFβ-SMAD1/5 signaling as well as formation of mixed SMAD complexes. Moreover, BMPR2-deficient cells express genes indicative of altered biophysical properties, including up-regulation of extracellular matrix (ECM) proteins such as fibrillin-1 (FBN1) and of integrins. As such, we identified accumulation of ectopic FBN1 fibers remodeled with fibronectin (FN) in junctions of BMPR2-deficient ECs. Ectopic FBN1 deposits were also found in proximity to contractile intimal cells in pulmonary artery lesions of BMPR2-deficient heritable PAH (HPAH) patients. In BMPR2-deficient cells, we show that ectopic FBN1 is accompanied by active β1-integrin highly abundant in integrin-linked kinase (ILK) mechano-complexes at cell junctions. Increased integrin-dependent adhesion, spreading, and actomyosin-dependent contractility facilitates the retrieval of active TGFβ from its latent fibrillin-bound depots. We propose that loss of BMPR2 favors endothelial-to-mesenchymal transition (EndMT) allowing cells of myo-fibroblastic character to create a vicious feed-forward process leading to hyperactivated TGFβ signaling. In summary, our findings highlight a crucial role for BMPR2 as a gatekeeper of endothelial homeostasis protecting cells from increased TGFβ responses and integrin-mediated mechano-transduction.